Pemasaran Jasa Pendidikan dalam Meningkatkan Brand Image di MI Al Kautsar Durisawo Ponorogo - Uliyatul Mukaromah; Wirawan Fadly (Pascasarjana IAIN Ponorogo, 2022)
Abstract The challenge for educational institutions now is increasing competition between institutions, so many educational institutions offer services. The increasing competition in the marketing of educational services between institutions at this time means that Islamic educational institutions should market education services in various ways. To maintain its quality and be able to deal with its institution, an educational institution must maintain the value of its existence or existence. Various exciting events occurred while carrying out education. When accepting new prospective students, the community is now starting to be smart in choosing educational institutions for their sons/daughters. So academic institutions must have a good image in the eyes of the community. To create a brand image for educational institutions, marketing services for education are needed, and the right strategy is to use the 7P marketing theory. MI Al Kautsar, in marketing education services, uses the marketing mix for education services. Based on this, a research was conducted with the limitation of research problems about how the form of marketing education services at MI Al Kautsar Durisawo Ponorogo, how the marketing mix of Education services at MI Al Kautsar Durisawo Ponorogo in improving the brand image of educational institutions, and how the positive impact of marketing on the brand image at MI Al Kautsar Durisawo Ponorogo. This study uses a qualitative educational research method, where the data that is explained does not use numbers but provides a descriptive description. In research activities using open interview data collection techniques, moderate participation observation, and documentation. From the research process, it was found that MI Al Kautsar did educational marketing services vigorously, and the results showed that in a short time, it was able to attract many students. The marketing mix of MI Al Kautsar's Education services has three curriculum bases: Ministry of Religion, Tahfidz, and Islamic Boarding Schools. It was found that the tariff was relatively cheap, strategically located in the city area but not on the edge of the main highway. Promotions are carried out offline and online, maximizing all madrasah residents with adequate facilities and infrastructure. The marketing of services carried out can attract public interest and impact the form of reasonable assumptions from the community. Abstrak Tantangan lembaga pendidikan kini yakni mulai meningkatnya persaingan antar lembaga, sehingga sangat banyak penawaran jasa lembaga pendidikan. Meningkatnya persaingan pemasaran jasa pendidikan antar lembaga saat ini, maka sudah seharusnya lembaga pendidikan Islam melakukan pemasaran jasa Pendidikan dengan berbagai cara. Suatu lembaga Pendidikan untuk dapat tetap menjaga kualitas dan mampu memasarkan lembaganya, makai a harus menjaga nilai keberadaannya atau eksistensinya. Beragam kejadian menarik saat melaksanakan Pendidikan, ketika penerimaan calon peserta didik baru masyarakat kini mulai pandai dalam memilih lembaga pendidikan untuk putra/putrinya. Maka lembaga pendidikan haruslah memiliki citra yang baik dalam pandangan masyarakat. Untuk menciptakan brand image lembaga pendidikan maka diperlukan pemasaran jasa pendidikan dan strategi yang tepat ialah menggunakan teori marketing 7P. MI Al Kautsar dalam pemasaran jasa pendidikan menggunakan bauran pemasaran jasa pendidikan. Berdasarkan hal tersebut maka dilakukan penelitian dengan batasan masalah penelitian tentang bagaimana bentuk pemasaran jasa Pendidikan di MI Al Kautsar Durisawo Ponorogo, bagaimana bauran pemasaran jasa Pendidikan di MI Al Kautsar Durisawo Ponorogo dalam meningkatkan brand image lembaga pendidikan, dan bagaimana dampak positif dari pemasaran terhadap brand image di MI Al Kautsar Durisawo Ponorogo. Penelitian ini menggunakan metode penelitian Pendidikan kualitatif, dimana data yang dijelaskan bukan menggunakan angka melaiankan pemaparan secara deskripsi. Dalam kegiatan penelitian menggunakan Teknik pengumpulan data wawancara terbuka, observasi partisipasi sedang dan dokumentasi. Dari proses penelitian tersebut ditemukan hasil bahwa MI Al Kautsar melakukan pemasaran jasa Pendidikan dengan giat dan hasilnya Nampak yaitu dengan waktu yang singkat mampu menarik banyak peserta didik. Bauran pemasaran jasa Pendidikan produk MI Al Kautsar memiliki 3 basis kurikulum: Kemenag, tahfiz, dan pesantren. Ditemukan tarif relatif murah, tempanta strategis daerah kota namun tidak berada di pinggir jalan raya utama. Promosi dilakukan dengan offline dan online, memaksimalkan semua warga madrasah, sarana dan prasarana memadai. Pemasaran jasa yang dilakukan mampu menarik minat masyarakat dan memberikan dampak berupa anggapan baik dari masyarakat. Keywords: Brand Image; jasa pendidikan; pemasaran